2018
DOI: 10.1142/s0219720018400176
|View full text |Cite
|
Sign up to set email alerts
|

Proposing drug fragments for dengue virus NS5 protein

Abstract: Dengue fever is a febrile illness caused by Dengue Virus, which belongs to the Flaviviridae family. Among its proteome, the nonstructural protein 5 (NS5) is the biggest and most conserved. It has a primer-independent RNA-dependent RNA polymerase (RdRp) domain at its C-Terminus. Zou et al. studied the biological relevance of the two conserved cavities (named A and B) within the NS5 proteins of dengue virus (DENV) and West Nile Virus (WNV) using mutagenesis and revertant analysis and found four mutations located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The exploration of multiple binding sites is of great importance in pharmacology ( Hetényi and Bálint, 2020 ; Yuan et al, 2020 ) and has been a strategy considered in various studies ( Hammoudeh et al, 2009 ; Ludlow et al, 2015 ). Most studies have focused on the function of NS5 as RdRp ( Troost and Smit, 2020 ) because this activity is absent in the host cell ( Galiano et al, 2016 ), and this is promising to design specific inhibitors with low toxicity ( El Sahili and Lescar, 2017 ); and within RdRp, cavity B has been considered a site to be explored for the drug design ( Malet et al, 2008 ; Alhossary et al, 2018 ); however, the MTase domain is also reported as an attractive strategy in the anti-flavivirus drug design ( Santos et al, 2020 ), and regions such as GTP and SAM pockets are obvious targets for antiviral development since they have both been shown to bind to low-molecular-weight ligands ( Lim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exploration of multiple binding sites is of great importance in pharmacology ( Hetényi and Bálint, 2020 ; Yuan et al, 2020 ) and has been a strategy considered in various studies ( Hammoudeh et al, 2009 ; Ludlow et al, 2015 ). Most studies have focused on the function of NS5 as RdRp ( Troost and Smit, 2020 ) because this activity is absent in the host cell ( Galiano et al, 2016 ), and this is promising to design specific inhibitors with low toxicity ( El Sahili and Lescar, 2017 ); and within RdRp, cavity B has been considered a site to be explored for the drug design ( Malet et al, 2008 ; Alhossary et al, 2018 ); however, the MTase domain is also reported as an attractive strategy in the anti-flavivirus drug design ( Santos et al, 2020 ), and regions such as GTP and SAM pockets are obvious targets for antiviral development since they have both been shown to bind to low-molecular-weight ligands ( Lim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like all polymerases, the structure of the RdRp of flaviviruses resembles a right hand with the characteristic subdomain fingers (amino acids 273- 315, 416-496, and 543- 600), palm (amino acids 497-542 and 601-705), and thumb (amino acid 706-900) ( Zou et al, 2011 ; Najera, 2013 ; Galiano et al, 2016 ). In addition, the RdRp domain is unique to RNA viruses, and it is absent in human cells; for this reason, the DENV NS5 protein is an attractive target in the search for antiviral compounds ( Malet et al, 2008 ; De Burghgraeve et al, 2013 ; Meguellati et al, 2014 ; Alhossary et al, 2018 ; Mirza et al, 2019 ). The crystal structure of the RdRp catalytic domain of DENV was reported by Yap et al , allowing the exploration of regions in its structure that could be of interest for the design of anti-dengue compounds ( Yap et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%